Post-Dissolution Friendships (PDFs) pada Dewasa Awal - Dina Aulia; Ika Andrini Farida (Jurnal Penelitian Kualitatif Ilmu Perilaku, 2021)
Post-dissolution friendships (PDFs) are phenomenon where a person becomes friend again with their ex-girl/boyfriend. PDFs are described as weak person, masochistic, and unable to adapt to their separation. On the other side, some people think that people in PDFs have higher level of adaptation than non-PDFs. PDFs is also considered as matured person. Therefore, this study aims to explain the phenomenon of PDFs, their impact, and their relation to developmental tasks and personality maturity in emerging adulthood. This study used a qualitative approach, phenomenological model. The research subjects were 6 people (3 in PDFs group and 3 in non-PDFs group) who were selected based on consideration criteria and had several different aspects between individuals. Data collection using the interview method regarding the phenomenon of PDFs, from the point of view of those who are PDFs and non-PDFs. To test the validity of this study, a data triangulation technique was used to the subject's ex-partner relationship.The results showed that a person wants to be friends with their ex because they wants to maintain a good relationship and avoid hostility. People in PDFs have the closest relationships with the most memorable ex. In addition, there is no empirical evidence that PDFs can have a negative impact. Instead, PDFs will have positive impacts. In emerging adulthood, people in PDFs reached more stages of psychosocial development and had more personality maturity.